Heavy metal concentration in cassava cultivated on re-vegetatively restored mined spoils at an Anglogold concession, Obuasi-Ghana - Abubakar, Muhammed (University of Cape Coast, 2015)
Mining is one of the main causes of environmental pollution by heavy metals. Re-vegetation of mine spoils is an effective way of restoring the mined land to its pristine status. The study was conducted to assess the physicochemical soil properties, heavy metal concentrations in two re-vegetatively restored mined spoils at an AngloGold concession at Obuasi. Concentration of heavy metals in cassava were used as an indicator for comparism. A simple random sampling technique was used to obtain soils at 0-15 cm depth and crop samples. Data analyses were done using GENSTAT statistical package. The results showed that the soil was slightly acidic, loamy textured, well aerated with a maximum bulk density of 1.33 Mg m-3. The mean maximum concentration values for K+, Ca2+, Mg2+, Na+ in the soil; 7.39, 12.72, 12.62, and 1.57 mg kg-1 respectively were very low. These were attributed to leaching losses and low level of organic carbon content of the soil. Also, the mean maximum concentrations of As, Cu, Fe, Mn, Pb and Zn levels in the soil were; 0.98, 34.50, 213.45, 56.11, 3.35 and 43.04 mg kg-1 respectively, while Cd was below detection. Metals detected in the soil were at higher concentrations compared to values in the cassava tubers. These values detected were however below phytotoxicity levels. Further studies on heavy metal accumulation in the cassava were suggested to be made at different seasons in order to help advise farmers on the consumption pattern of the crop.
xii,126p:, ill
Keywords: Heavy metal Mined spoil Mined spoil reclamation Phytotoxicity Re-vegetation Translocation factor